Linkages between Foreign Direct Investment, Domestic Investment and Economic Growth: Evidence from Nigeria - Ringim, Salim Hamza (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
FDI is the purchasing of an existing company or establishing a new company in a foreign country Rutherford (1992), according to modernization theories FDI can enhance growth in less developed countries but the dependency theorists contend that dependence on foreign investment is expected to affect the growth and income distribution negatively. Also FDI can crowd out or crowd in domestic investment depending on the sector FDI is allocated to and also depending on the country. This research is conducted base on this argument. This research empirically analyzed the linkages between foreign direct invest, domestic investment and economic growth in Nigeria. The research is conducted using annual time series data from the period of 1980 to 2013. The study employs Johansen multivariate cointegration test and Vector Error Correction model (VECM) as the estimations techniques. The result of the study reveals that foreign direct investment (FDI) domestic investment (DI) and economic growth have a long-run equilibrium relationship according to the Johansen Multivariate cointegration test. And the VECM result shows that the speed of adjustment of the variables towards their long-run equilibrium is 52.55%. Keywords: Foreign Direct Investment (FDI), Domestic Investment (DI), Economic growth, Nigeria, Time series, Cointegration, Vector error correction model (VECM).

ÖZ: DYY, mevcut bir şirketin satın alınması veya yabancı bir ülkede yeni bir şirket kurmasıdır Rutherford (1992), Modernleşme teorilerine göre DYY az gelişmiş ülkelerde büyümeyi artırabilir ancak bağımlılık teorisyenleri, yabancı yatırıma bağımlılığın büyüme ve gelir dağılımını olumsuz etkilemesi beklenmektedir. Ayrıca, doğrudan yabancı yatırımlar, ülkeye bağlı olarak ve doğrudan yabancı yatırıma tahsis edilen sektöre bağlı olarak, yerli yatırımlarda kalabalığa veya kalabalığa neden olabilir. Bu araştırma, bu kanıta dayanarak yürütülmektedir. Bu araştırma, doğrudan yabancı yatırım, yerli yatırım ve Nijerya'daki ekonomik büyüme arasındaki bağlantıları deneysel olarak analiz etmiştir. Araştırma 1980'den 2013'e kadar olan yıllık zaman serisi verilerini kullanarak gerçekleştirildi. Araştırma, tahmin teknikleri olarak Johansen çok değişkenli eş-bütünleşme testi ve Vektör Hata Düzeltme Modeli (VECM) kullanmaktadır. Araştırmanın sonucunda, yabancı doğrudan yatırım (DYY) yerel yatırımın (DI) ve ekonomik büyümenin, Johansen Çok Değişkenli eş bütünleşme testine göre uzun dönemli bir denge ilişkisine sahip olduğu ortaya çıkmaktadır. Ayrıca VECM sonucu, değişkenlerin uzun dönem dengelerine doğru hızlanma oranının% 52.55 olduğunu göstermektedir. Anahtar kelimeler: Doğrudan yabancı yatırımı (DYY), yurtiçi yatırım(DI), Ekonomik büyüme, Nijerya, zaman serisi, eşbütünleşme, vektör düzeltme modeli(VECEM).
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2017. Supervisor: Assoc. Prof. Dr. Hasan Güngör.
Keywords: Economics; Nigeria-Economic Growth; Economic Conditions and Development-Nigeria; Investments-Business-Nigeria; Foreign Direct Investment (FDI); Domestic Investment (DI); Economic Growth; Nigeria; Time Series; Cointegration; Vector Error Correction Model (VECM)